ARTIKEL REVIEW : PENGETAHUAN REMAJA TERHADAP PENCEGAHAN INFEKSI MENULAR SEKSUAL - Andwika Satya Yuniart; Dela Safitri; Wilda Nuraini Subagio (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Sexually Transmitted Infections (STIs) remain a major reproductive health issue affecting adolescents in various countries. Lack of knowledge, negative attitudes, and risky behaviors make adolescents vulnerable to HIV and AIDS, gonorrhea, and syphilis. Health education has been shown to improve knowledge and positive attitudes, but gaps remain, particularly among adolescents with disabilities and those in areas with limited health services. This literature review aims to analyze adolescents' knowledge and attitudes toward STI prevention based on three international studies in Indonesia and Zambia. The method used was a quantitative or descriptive research design and a literature review of three internationally indexed scientific articles. The results indicate that adolescents' knowledge of STIs remains low to moderate. Comprehensive, inclusive, and school-based sexual health education interventions are needed to encourage changes in STI prevention behavior among adolescents.